ASSESSMENT OF THE POLYMORPHIC GENES VARIANTS OF THE LIPID AND CARBOHYDRATE METABOLISM, VASCULAR INFLAMMATION AND NEUROTRANSMITTER SYSTEM IN THE FIRST ISCHEMIC STROKE - V. N. Shishkova; A. Yu. Remennik; V. N. Valyaeva; V. M. Shklovsky; T. V. Adasheva (Кардиоваскулярная терапия и профилактика, 2017)
Aim. To study the relations of polymorphic variants of the genes: АРОЕ, MTHFR, IL8, IL6, TNF-а, VEGFA, ADIPOQ, ADIROR, APOB, APOА-V, APOC-IV, LPL, LP(a), BDNF, GRM1, GRM3 and development of the first ischemic stroke (IS).Material and methods. The alleles frequencies and genotypes assessed for 20 mono-nucleotide polymorphic gene variants in 435 patients, who had first IS, and 229 persons with no stroke, comparable with age, gender, place of living and ethnicity. Genotyping of polymorphisms was done with the prepared TaqMan probes.Results. For polymorphisms АРОВ (rs676210) and IL8 (rs1803205) there was significant difference between groups in the variety of minor alleles and genotypes.Conclusion. There is significant relation of mononucleotide polymorphisms of the genes АРОВ (rs676210) and IL8 (rs1803205) with the development of first IS in the studied groups.